(untitled) (Journal of the College of Education for Women, 2019)
Kant defines the science of beauty as the criticism of taste judgments, and critical judgments of the beauty can not be classified under the mental principles. Also the rules that are provided do not have any advantage to any science. And the taste judgments can not be directed as rules, which mean. They belong to sensory epitomology. Taste can not be only under the subjective principle, which means that to imagine the subject through this principle and we can conclude that this subject is beautiful, if we do this, we would made the judgment a science, and here it will become a taste judgment. thus, according to Kant the taste judgments are related to beauty, and every thing which leads it. It is clear from his early study of the science of beauty, in writing about the feeling of the graceful and the beauty Kant considered the graceful and the beauty are contradictory. The graceful is connected with fear, and have tension while the beauty’s pleasure as a result of feeling in love and salisfaction and relaxation.